Antioxidant CPA-type indole alkaloids produced from the deep-sea derived fungus Aspergillus sp. SCSIO 41024. Issue 23 (2nd December 2021) - Chen, Wei-Hao; Li, Kun-Long; Lin, Xiu-Ping; Liao, Sheng-Rong; Yang, Bin; Zhou, Xue-Feng; Wang, Jun-Jian; Liu, Yong-Hong; Wang, Jun-Feng
Abstract: Twelve indole alkaloids, including α-cyclopiazonic acid (CPA) (1 ), nine 2-oxo indole CPA derivatives (2 –10 ), and two open-ring indole CPA derivatives (11 and 12 ), were isolated from the fermentation broth of a deep-sea derived fungus Aspergillus sp. SCSIO 41024. Their structures and absolute configurations were elucidated mainly by using extensive NMR spectroscopic, mass spectrometric and single crystal X-ray diffraction analysis. To the best of our knowledge, the crystallographic data of 3 and 7 were firstly reported, and the absolute configuration of 3 was confirmed for the first time by the single crystal X-ray diffraction analysis. Most isolated compounds were tested for their antimicrobial, antitumor and radical scavenging activities. In addition, compounds 1, 2 and 11 showed moderate antioxidative activity against DPPH with IC50 values of 190.1, 31.9, 228.4 μg/mL, respectively. Graphical Abstract: